Opini Pemilih Pemula Surabaya terhadap Iklan Politik Para Kandidat di Pilkada - Agusly Irawan Aritonang (Fakultas Ilmu Komunikasi UKWMS, 2020)
Election Campaign Period is a period in political events where candidates have the opportunity to introduce themselves to the public. Through various forms and channels of communication, candidates endeavor to convey their ideas and profile. One form of communication channel is political advertising. The target group that is always interesting to be targeted by advertisements is the beginner voter group. With a very significant number of them, the beginner voter is a potential